Community as a Transformative Civic Education Curriculum in Higher Education to Strengthen Civic Engagement in the Digital Era - Aina Nurdiyanti; Muh Khaedir (Universitas Negeri Gorontalo, 2026)
The crisis of civic engagement among university students in the digital era represents one of the most urgent challenges facing contemporary democratic societies. Although digital transformation has expanded channels for participation, it has also intensified apathy, polarization, slacktivism, and clicktivism among young citizens, particularly within Indonesia's post-Reformasi democratic landscape. This article examines why the current Pancasila and Citizenship Education (PKn) curriculum in higher education has not yet effectively cultivated civic engagement and proposes a community-based transformative curriculum model as a response. Using a Systematic Literature Review (SLR) guided by the PRISMA framework, this study synthesizes 68 Scopus-indexed articles published between 2023 and 2026 through thematic and content analysis. The theoretical framework integrates civic engagement theory, curriculum reconstruction theory, experiential learning, service-learning, democratic culture, and Pancasila as civic philosophy. The findings reveal five major thematic gaps: theoretical fragmentation between rational and sensibility-based engagement, insufficient digital citizenship education, weak community partnership models, limited culturally sustaining pedagogy, and inadequate assessment frameworks. The study proposes the Community-Based Civic Empowerment (CBCE) curriculum model, which positions community as a living curriculum laboratory within the Mandatory General Education (MKWK) framework. The model operationalizes Pancasila values through collaborative civic action, project-based digital citizenship, deliberative democracy practices, and multidimensional assessment. It contributes theoretically to civic education curriculum studies and practically to higher education policy for transformative democratic education.